Liminal Ambidexterity: Organizing Between Executional Simplicity and Adaptive Complexity in Transitional Environments - Skučaitė, Gabija; Recai Uygur, Mehmet (Transformations In Business & Economics, 2026)
This conceptual paper develops the notion of liminal ambidexterity to explain how organizations remain effective when their established routines continue to support performance but cease to orient them toward future advantage. Using concepts such as ambidexterity, liminality, dynamic capabilities, resilience, and management control, the paper argues that transitional environments require firms to maintain executional simplicity in the operational core while creating sufficient adaptive complexity at the edge. The framework recognizes three indexed domains: the Simplicity Discipline Index (SDI), the Complexity Capability Index (CCI), and the Complexity Load Index (CLI). In addition, translational governance is introduced as a mechanism that converts ambiguous signals into a limited set of executable commitments. The paper contributes a quadrant model, a capability-load fit logic, a refined definition of translational governance, illustrative empirical anchors, and a measurement architecture for future empirical testing.